Metode gross up dalam perhitungan Pajak Penghasilan pasal 21 - Burhan, Imron; Sari, Sri Nirmala; Saleh, Fadilah Indrayanti (PT Bone Jaya Kreatif, 2022)
This study aims to determine the analysis of calculations using the gross up method. The method used in this research is qualitative which aims to provide an overview of a situation that is the focus of research conducted by researchers. The result of the calculation analysis between the gross up method is that the application of the gross up method is very beneficial for both parties. For employees, the amount of the tax allowance will be added to the employee's income where the income received by the employee can be received in full without any reduction in Article 21 income tax, while for companies the burden arising from the provision of allowances is a deductible expense and is able to streamline the company's tax burden. The application of the gross up method is able to reduce the income tax article 21 owed by employees, as well as increase the income received by individual employee taxpayers